Effectiveness of Activated Zeolite in Reducing Iron (Fe) and Zink (Zn) Metal Levels in Borehole Water - Zul Alfian; Ronaldo Sensini Siregar (Talenta Publisher, 2023)
Research has been carried out on the adsorption of iron (Fe) and zinc (Zn) metal levels using activated zeolite with acid and base in healthy water. Characterization was carried out on activated zeolite using X-ray Fluorescence (XRF). Samples were taken from borehole water from Puji Mulyo area, Deli Serdang, and preserved with HNO3 until pH < 2, then digested. Determined the concentration of iron (Fe) and zinc (Zn) before and after the addition of activated zeolite by NaOH and HCl using an Atomic Absorption Spectrophotometer (AAS) with length-specific waves are 248.3 nm for iron (Fe) and 213.9 nm for zinc (Zn) metal. The results showed that the concentration of iron (Fe) and zinc (Zn) in the borehole water after the addition of activated zeolite decreased. Zeolite activated by NaOH absorbs iron (Fe) metal by 68.60% and absorbs zinc (Zn) metals by 37.91%. Meanwhile, Zeolite activated by HCl absorbs iron (Fe) by 42.37% and absorbs zinc (Zn) metal by 15.17%. This research shows that the effectiveness of percentage (%) decreasing the concentration of iron (Fe) and zinc (Zn) metal using activated zeolite with NaOH was more significant and more effective than activated zeolite with HCl.